Acylation of isobutylbenzene with acetic anhydride on AlKIT-6 mesoporous acid catalyst - Prabhu Azhagapillai (KeAi Communications Co., Ltd., 2021)
Aluminium substituted mesoporous KIT-6 materials were directly synthesized by hydrothermal method with different silica to aluminium ratios (Si/Al = 25, 50, 75, 100). These materials were obtained by using Pluronic P123 and n-butanol as a structure-directing agent and co-solvent respectively, under high acidic conditions. The prepared catalysts were characterized by small-angle XRD, ICP-AES, nitrogen sorption analysis, TGA, SEM, TEM, and XPS techniques. The characterization revealed that aluminium is mainly incorporated into the framework of KIT-6. The XRD patterns and TEM images of materials showed a highly ordered cubic Ia3d mesostructure. The incorporation of the aluminium was clearly evident from XPS and ICP-AES techniques. Further, the synthesized Al-KIT-6 catalysts were tested in the acylation of isobutylbenzene (IBB) with acetic anhydride (AA). The results revealed that Al-KIT-6 (25) was a prominent active catalyst due to silica to aluminium ratio than others. The catalytic reaction conditions were tuned to obtain a high selectivity of 4-isobutyl acetophenone (4-IBA) with high conversion of isobutylbenzene. Al-KIT-6 (25) showed a high conversion (72%) of isobutylbenzene and 94% selectivity of 4-isobutyl acetophenone.